Coping Strategies, Personality Type, and Help-seeking behavior for Mental Health Problems - Marleny Purnamasary Panis; Yeni Damayanti; Marselino K. P. Abdi Keraf (Universitas Nusa Cendana, 2019)
Individual dispositions and personal factors play a role in determining the strategy to cope with mental health problems. Individuals with type A personality often show greater effort to improve their condition when experiencing stress. The study used 75 participants all gained through convenience sample ages 18-35 years old most of whom were university students in Kupang. The study used the General Help-Seeking Questionnaire (GHSQ), Ways of Coping, and stress-prone type A personality test to investigate different coping strategies of individuals with type A personality when seeking help for mental health problems. Data analysis using Pearson's product-moment correlation shows significant findings to support hypotheses that coping strategies are related to certain help-seeking behavior in individuals with type A personality (p=<0.05; 2-tailed). The awareness of important roles of personality tendencies when seeking help for mental health problems will impact on matters related to stress-reduction efforts to achieve mental health and well-being.